2017
DOI: 10.1590/1414-431x20176177
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of CIB4 gene and protein in Kermani sheep

Abstract: The human calcium- and integrin-binding protein (CIB) family is composed of CIB1, CIB2, CIB3, and CIB4 proteins and the CIB4 gene affects fertility. Kermani sheep is one of the most important breeds of Iranian sheep breeds. The aim of this study was to analyze for the first time molecular characteristics of the CIB4 gene and protein in Kermani sheep. Different tissues were collected from the Kermani sheep and real time PCR was performed. The PCR products were sequenced, comparative analyses of the nucleotide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 30 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Growth and reproductive performance of indigenous sheep could be improved through improvement of genetics and environment [5]. However, growth and reproductive performance of indigenous sheep was influenced by most of the non-genetic factors [33,34] and it is thus appropriate to consider the factors affecting their outcome.…”
Section: Growth Performance and The Effect Of Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth and reproductive performance of indigenous sheep could be improved through improvement of genetics and environment [5]. However, growth and reproductive performance of indigenous sheep was influenced by most of the non-genetic factors [33,34] and it is thus appropriate to consider the factors affecting their outcome.…”
Section: Growth Performance and The Effect Of Factorsmentioning
confidence: 99%
“…The increased domestic and international demand for Ethiopian sheep and goats has established them as important sources of Inland Revenue as well as foreign currency [3]. Therefore, integrated attempt with emphasis on prescribing and genetic enhancement is crucial for improving animal output by improving growth and fertility traits [5]. In Ethiopia, there are 32.85 million sheep, more than 99% of which are indigenous [6].…”
Section: Introductionmentioning
confidence: 99%
“…Small ruminants, particularly native local breed types, play a significant socio-economic role in ensuring the livelihoods of a considerable portion of human populations in the tropics [1][2][3], and genetic manipulations in improving ewe production and reproduction present valuable opportunities to increase financial revenue [4][5][6][7][8]. Sudan harbors different sheep breeds referred to as the Sudanese Desert sheep which are distinguished according to the different Sudanese tribes that rear them such as the Dubasi, Shugor, and Watish breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Species without sufficient genetic variability and diversity face more challenges in efficiently adapting to environmental fluctuations as they become less resilient and more susceptible to diseases [17,18]. Thus, preserving genetic diversity in indigenous breeds is a major concern during the design of selection programs to improve productive traits of a specific breed without diluting or losing other beneficial traits [7]. As conservation is dependent on deep and full knowledge of the genome of a specific breed [19], it is important to try to genetically characterize indigenous breeds [14] and to determine the applications of molecular genetics [20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to CIB1 and CIB2, the functions of CIB3 or CIB4 remain unclear. It has been shown that Cib4 is expressed specifically in the testis in sheep [ 22 , 23 ], suggesting that CIB4 may play a role in male fertility. In this study, we mutated Cib4 using the CRISPR/Cas9 system and analyzed its function in mice.…”
Section: Introductionmentioning
confidence: 99%